2013
DOI: 10.1093/hmg/ddt516
|View full text |Cite
|
Sign up to set email alerts
|

Sex-biased methylome and transcriptome in human prefrontal cortex

Abstract: Brain function and cognitive performance differ between men and women in some measures. The phenotypic variation may be partially due to sex differences in epigenomes and transcriptomes in specific brain regions [e.g. the prefrontal cortex (PFC)]. Genome-wide DNA methylation and gene expression were examined in postmortem PFC of 32 males and 14 females (all were Caucasians) using Illumina's 450K Methylation and HT-12 v4 Gene Expression BeadChips, respectively. Multiple linear regression, Pearson correlation an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
144
0
4

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 146 publications
(161 citation statements)
references
References 38 publications
13
144
0
4
Order By: Relevance
“…For example, Tsai et al reported sex differences in histone acetylation in neonatal mouse brain [26]. Similarly, Xu et al have demonstrated sex bias in the methylome and transcriptome of the human prefrontal cortex [27]. We recently reported on sex differences in genome-wide DNA methylation in newborns [28].…”
mentioning
confidence: 61%
“…For example, Tsai et al reported sex differences in histone acetylation in neonatal mouse brain [26]. Similarly, Xu et al have demonstrated sex bias in the methylome and transcriptome of the human prefrontal cortex [27]. We recently reported on sex differences in genome-wide DNA methylation in newborns [28].…”
mentioning
confidence: 61%
“…Eckhardt et al, using 2,524 autosomal loci, could not detect any statistical differences between male and female samples from 12 different tissues [33]. Among the studies investigating human brain tissue, two showed more hypermethylated autosomal sites in females than in males [18,34], and two studies on the chromosomes was also noted in a study on mice brain [22]. Higher prevalence of sex-biased methylation sites on different chromosomes could be potentially linked to sex-specific functions of the genes on these chromosomes.…”
Section: Resultsmentioning
confidence: 97%
“…Evidence suggests that only rarely do differences in DNA methylation at a single site relate to measureable differences in gene expression. In a recent whole-genome study of sex differences in DNA methylation in the human prefrontal cortex, for example, about 6% of the CpG sites that were differentially methylated in men and women correlated with a sex difference in transcription [53]. The odds get a little better going in the other direction: starting with a significant sex difference in gene transcription, a significant difference in DNA methylation was found about 35% of the time (but even then, only three-fourths of those were in the predicted direction) [53].…”
Section: (B) Mechanisms For Demethylation Are Now Establishedmentioning
confidence: 99%